Roots Tourism–Whose Roots? The Marginalization of Palestinian Heritage Sites in Official Israeli Tourism Sites - Kadman, Noga (Téoros, 2010)
Israel is the contested homeland of both the Jewish-Israeli and the Arab-Palestinian peoples. In the practice of tourism, Israel highlights sites of Jewish history and tends to neglect those of Palestinian history.Many of the Palestinian villages and heritage sites were destroyed by Israel in 1948 and onwards, or were gradually dilapidated due to lack of official care. Large-scale Palestinian roots tourism does not exist, due to the impossibility of most Palestinians to gain access into Israel.This paper explores an unusual form of roots tourism: the encounter between Jewish-Israelis and Palestinian depopulated villages that are located today within the boundaries of Israeli tourist sites. The paper demonstrates that the villages are largely ignored or marginalized in the information given to the public. The tourism authorities therefore underestimate the roots of the Palestinians in the country and portray an overall picture of a Jewish country, with very minor Arab heritage.